Evaluasi akuntabilitas dan transparansi pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) Desa Pineleng Dua Indah Kecamatan Pineleng - Kawatu, Avelina Setyadeo Frerivili; Tirayoh, Victorina Z; Datu, Christian (Riset Akuntansi dan Portofolio Investasi, 2024)
Accountability can be interpreted as the embodiment of the duty of village government officials to be responsible for the management of village funds to achieve predetermined goals efficiently, effectively, and economically. The purpose of this research is to assess the accountability of Village Revenue and Expenditure Budget or APBDes in Pineleng Dua Indah Village and to assess the transparency of APBDes in Pineleng Dua Indah Village. This research was conducted in Pineleng Dua Indah Village, Pineleng District, Minahasa Regency using the descriptive analysis method, which is a type of data analysis used to describe, present, and summarise a set of data. The research found that the practice of village financial management in Pineleng Dua Indah Village shows good efforts to improve transparency, and accountability in the village’s financial decision-making process.